2008
DOI: 10.1007/978-3-540-68679-8_43
|View full text |Cite
|
Sign up to set email alerts
|

Specifying and Analysing SOC Applications with COWS

Abstract: Abstract. COWS is a recently defined process calculus for specifying and combining service-oriented applications, while modelling their dynamic behaviour. Since its introduction, a number of methods and tools have been devised to analyse COWS specifications, like e.g. a type system to check confidentiality properties, a logic and a model checker to express and check functional properties of services. In this paper, by means of a case study in the area of automotive systems, we demonstrate that COWS, with some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Since its definition, a number of methods and tools have been devised to analyse COWS specifications, such as a type system to check confidentiality properties [18], a logic and a model checker to express and check functional properties of services [12], a stochastic extension to enable quantitative reasoning on service behaviours [23], a static analysis to establish properties of the flow of information between services [2], and bisimulation-based observational semantics to check interchangeability of services and conformance against service specifications [24]. An overview of some of the above tools, with an application to the analysis of a case study, can be found in [19].…”
Section: Related Work and Concluding Remarksmentioning
confidence: 99%
“…Since its definition, a number of methods and tools have been devised to analyse COWS specifications, such as a type system to check confidentiality properties [18], a logic and a model checker to express and check functional properties of services [12], a stochastic extension to enable quantitative reasoning on service behaviours [23], a static analysis to establish properties of the flow of information between services [2], and bisimulation-based observational semantics to check interchangeability of services and conformance against service specifications [24]. An overview of some of the above tools, with an application to the analysis of a case study, can be found in [19].…”
Section: Related Work and Concluding Remarksmentioning
confidence: 99%
“…Due to their rich repertoire of elegant meta-theories, proof techniques and analytical tools, process calculi currently play a central role in laying rigorous methodological foundations for specification and validation of SOC applications. Our preference for COWS is motivated by its mechanisms and primitives that have proven to be particularly expressive for modeling the behavior of serviceoriented applications (see, e.g., [24], [25]). Moreover, the calculus is equipped with tools for formulating properties of COWS specifications and demonstrating their validity, like the temporal logic SocL and its model checker CMC [17] that we use in our investigation.…”
Section: Specification and Analysismentioning
confidence: 99%
“…Analytical results for Web Services transactions are important; in particular, it is vital to verify that the various reductions to the ACID properties work correctly. Theoretical models have been developed to allow such verification (Fantechi et al, 2009;Mayer et al, 2008;Lapadula et al, 2008), but these models do not easily allow direct comparison between different transaction techniques. The models can indicate whether techniques are valid, but cannot always indicate the application for which (and environment in which) a technique is most beneficial.…”
Section: Simulating Web Services Transactionsmentioning
confidence: 99%